2011
DOI: 10.1002/j.2050-0416.2011.tb00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Single Kernel NIR Barley Protein Calibration and Assessment of Variation in Protein on Grain Quality

Abstract: In this paper, we describe results from a preliminary experiment on the development of a near infrared reflectance (NIR) calibration for single kernel (SK) % protein content in barley. The SKNIR calibration was developed using kernels from breeding lines and commercial barley varieties with a range in protein content of 7.3% to 16.6% "as is" . The calibration model produced an R 2 = 0.903, while the validation set had a R 2 = 0.837 with a standard error of cross validation and a standard error of prediction of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
4
12
0
Order By: Relevance
“…The production of wort and its subsequent analysis is time consuming so less expensive and rapid predictive methods have been utilized. Near‐infrared spectroscopy has been used for decades to predict barley malt traits associated with improved quality including in single grains of barley and starch, proteins and lipids in barley grain, malt and wort . Near‐infrared spectroscopy has been used to predict malt and wort quality and beer quality but its use in breeding programmes is where is has the greatest value .…”
Section: Introductionmentioning
confidence: 99%
“…The production of wort and its subsequent analysis is time consuming so less expensive and rapid predictive methods have been utilized. Near‐infrared spectroscopy has been used for decades to predict barley malt traits associated with improved quality including in single grains of barley and starch, proteins and lipids in barley grain, malt and wort . Near‐infrared spectroscopy has been used to predict malt and wort quality and beer quality but its use in breeding programmes is where is has the greatest value .…”
Section: Introductionmentioning
confidence: 99%
“…Typical analysis of barley protein content is on bulk samples with 1000 s of grains in the sample tested. However, several studies have shown NIR has the capacity to scan and predict single grains and from that data show the distribution of protein content in a sample [21][22][23]. These studies showed variation between single kernels within a spike of barley as well as variation in other quality parameters based on grains sorted into sub-groups of protein content.…”
Section: Proteinmentioning
confidence: 99%
“…SK‐NIR calibrations for protein content in wheats have shown similar levels of accuracy in other grains, including maize protein content and amino acid content in maize . In barley, protein content of individual kernels varied within a spike . In addition, one study reported sorting 4000 barley kernels into five protein sub‐samples; those sub‐samples (20–30 g) were then used to predicted other barley traits using conventional bulk NIR calibrations …”
Section: Applications For Cerealsmentioning
confidence: 99%
“…24 In barley, protein content of individual kernels varied within a spike. 25,26 In addition, one study reported sorting 4000 barley kernels into five protein sub-samples; those sub-samples (20-30 g) were then used to predicted other barley traits using conventional bulk NIR calibrations. 25 One of the key aspects in developing NIR calibrations are the reference methods.…”
Section: Protein Contentmentioning
confidence: 99%